IMPROVING TEACHER ABILITY IN TARGETED SCHOOLS IN MAKING RPP THROUGH GROUP GUIDANCE PEER TEACHER TUTOR BASED - Rais Happy (International Journal of Innovations in Engineering Research and Technology, 2021)
This research is a school action research that aims to improve teacher competence in making lesson plans or lesson plans with the approach used is peer teacher tutoring. The implementation of the research was carried out on teachers in the fostered supervisory environment in the Kota Timur sub-district, especially teachers whose schools were either schools that had affected K.13 or were still using KTSP. The implementation of the research was focused on KKG Cluster 2, Kota Timur District, involving 12 classroom teachers. the increase in competence in cycle 2 is 70% while the achievement indicator is 65%. Observations were made to obtain research data by direct observation of the steps in preparing the RPP based on the applicable regulations, namely the Regulation of the Minister of Education and Culture of the Republic of Indonesia No. 41 of 2007 for the 2006 Curriculum and Permendikbud No. 22 of 2016 for the 2011 Curriculum3.